A review on traditional villages protection and development in China - Hua, Z. Z.; Jamaludin, Omar; Doh, Shu Ing (Penerbit UMP, 2024)
Traditional villages serve not only as a habitat for inhabitants to grow and dwell but also as a significant domain for the preservation of historical and cultural legacy, bearing the fond memories of local residents and accumulating substantial economic and cultural worth. The advancement and fostering of traditional villages constitute a primary objective within the contemporary academic realm. Drawing upon data extracted from the Scopus database spanning from 2007 to 2024, this study undertook a comprehensive examination and structural analysis of pertinent research concerning the safeguarding and progression of Chinese traditional villages through data aggregation and synthesis. The outcomes of the investigation are outlined as follows: (1) Areas of focus in research on the safeguarding and advancement of Chinese traditional villages encompass spatial arrangement, assessment frameworks, and the promotion of tourism. A consensus has also been reached regarding the essence of traditional village preservation: primary stakeholders in the preservation process should include government entities, businesses, scholars, residents, and other involved parties, the focal point of preservation should be the village core, the fundamental phase of preservation and advancement revolves around categorized evaluation, and the approach to safeguarding and development involves the revitalization and activation of the village. Spatial pattern research methodologies encompass GIS spatial analysis, space syntax, data compilation, and assessment, while evaluation techniques include the Delphi method, analytic hierarchy process, and fuzzy comprehensive evaluation. (2) The existing research on the evolving landscape of traditional villages is deemed inadequate, lacking a comprehensive framework to provide guidance, and largely concentrated within a specific research scope. (3) Subsequent research endeavours should employ systematic frameworks to delve deeply into the study of traditional villages that are in a state of development but lack distinct characteristics. Addressing the issue of traditional villages' lack of vibrancy and fostering the resilience of traditional villages are vital objectives for future research.